THU0221 DRY EYE IN SJÖGREN'S SYNDROME: CHEMOKINE AND CYTOKINE TEAR SPECTRUM. (June 2019) - Hernandez-Molina, Gabriela; Ruiz-Quintero, Narlly; Lima, Guadalupe; Hernández-Ramírez, Diego; Llorente-Chavez, Amaya; Saavedra-González, Vanessa; Jimenez-Soto, Rodolfo; Llorente, Luis
Abstract : Background: Previous studies have linked the participation of multiple chemokines and cytokines in the physiopathology of primary Sjögren's syndrome (PSS), however data regarding their presence in tears is scarce Objectives: To evaluate a panel of chemokines/cytokines in the tears of patients with PSS and correlate them with ocular symptoms as well as objective ocular tests. Methods: We included 21 patients with PSS (EULAR/ACR criteria). A single expert ophthalmologist in dry eye evaluated the patients and assessed the tear film break-up time, Schirmer-I test, tear meniscus height, the Van Bijsterveld staining score and the SICCA Ocular Staining Score (OSS). We classified lacrimal dysfunction severity in two categories (1=mild, mild/moderate or moderate, and 2= moderate/severe and severe). We scored the ESSPRI, and ocular dryness VAS as well as the Ocular Surface Disease Index (OSDI), a 12-item scale for the assessment of symptoms related to dry eye disease and their effect on vision. Tear samples were collected using sterile tear flow strips, that were immediately frozen at -86°C until assayed. Once defrosted, the tears were extracted from the strips using a buffer containing 0.5 M NaCl and 0.5% Tween-20. We tested IFN-γ, IL-10, IL-12, IL-17A, IL-1β, IL-2, IL-21, IL-23, IL-5, IL-6, IL-8, TNF-α, BAFF, CXCL10 and CCL2 by Luminometry. We also included 21 healthy controls without dry eye, to test chemokines/cytokines that after our initial screening were meaningful. Results: Most patients were females (90.4%), mean age 59.3±13 years and median disease duration 7.9 years (0.5-27). All of them had ocular and oral symptoms. The median tear film break-up time was 6 seconds (2-9), median Schirmer-I test 6 mm (1-25), median lacrimal meniscus height 1.5 mm (0.5-2), median Van Bijsterveld staining score 10 points (2-18), median OSS 7 points (2-11), median ESPPRI score 6.7 points (2-9.2) and median ocular dryness EVA score 9 points (1-10). We did not detect most of the evaluated chemokines/cytokines with the exception of IL-8, CXCL10, and CCL2. The former was similar in both, patients and controls. PSS patients had lower levels of CXCL10 (472.8 pg/μL vs 1652 pg/μL, p=0.01) and CCL2 (1.08 pg/μL vs 9 pg/μL) than controls. Indeed, patients with worst lacrimal dysfunction severity had the lowest levels of CXCL10 (239.3 pg/μL vs. 646.2 pg/μL, p=0.02). We found correlations among CXCL10 and CCL2 (T=0.30, p=0.02) and lacrimal meniscus height (T=0.55, p=0.005), as well as with CCL2 and lacrimal meniscus height (T=0-57, p=0.01). None of the other variables were correlated. Conclusion: We identified CXCL10 and CCL2 as the main chemokines in tears of patients with PSS. CXCL10 seems to participate in the normal eye homeostasis. Disclosure of Interests: None declared